Experimental and theoretical insights in the alkene–arene intramolecular π-stacking interaction - Corne, Valeria (2016)
Fil: Fil: Corne, Valeria. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario (IQUIR–CONICET); Argentina.